A Meta-Analysis of Job Satisfaction Correlates in the Public Administration Literature. (June 2016) - Cantarelli, Paola; Belardinelli, Paolo; Belle, Nicola
What can we learn by applying a meta-analysis to the public administration literature on job satisfaction? More generally, how can public management scholars use this method to capitalize on the decades of research on other topics within our field? This study reports the findings of the first quantitative review of the public administration literature on job satisfaction. We retrieved quantitative data from primary studies published in 42 public administration journals since 1969 and performed a meta-analysis of the relationships between job satisfaction and 43 correlates. The findings include meta-analytically derived effect sizes, measures of the heterogeneity in the effect size underlying all primary studies, and several indicators of publication bias. In presenting the results of our meta-analysis, we address the merits and limitations of this methodology and discuss how public administration scholars could take full advantage of this information to advance knowledge in other areas within the field.